2018
DOI: 10.1111/acel.12773
|View full text |Cite
|
Sign up to set email alerts
|

Restoring mitochondrial DNA copy number preserves mitochondrial function and delays vascular aging in mice

Abstract: SummaryAging is the largest risk factor for cardiovascular disease, yet the molecular mechanisms underlying vascular aging remain unclear. Mitochondrial DNA (mtDNA) damage is linked to aging, but whether mtDNA damage or mitochondrial dysfunction is present and directly promotes vascular aging is unknown. Furthermore, mechanistic studies in mice are severely hampered by long study times and lack of sensitive, repeatable and reproducible parameters of arterial aging at standardized early time points. We examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 32 publications
3
68
1
1
Order By: Relevance
“…However, on the basis of our results we might infer that mtDNA copy number shows a functional threshold effect and below it might causes cellular dysfunction. In this regard, Foote and co‐workers have recently described a role of mtDNA‐mediated mitochondrial dysfunction in cardiovascular disease . They identify that mtDNA copy number directly regulate the onset and progression of vascular aging in mice .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…However, on the basis of our results we might infer that mtDNA copy number shows a functional threshold effect and below it might causes cellular dysfunction. In this regard, Foote and co‐workers have recently described a role of mtDNA‐mediated mitochondrial dysfunction in cardiovascular disease . They identify that mtDNA copy number directly regulate the onset and progression of vascular aging in mice .…”
Section: Discussionsupporting
confidence: 72%
“…Possible explanation is that a fraction of non‐functional mtDNA is present within the total population or is a component of non‐functional mitochondria. Conversely, it has been recently demonstrated that augmenting mtDNA copy number enhances mitochondrial respiration, opening a path for a possible treatment target. Further studies using neuronal cells are necessary to confirm the direct effect of mtDNA copy number in mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…Altered mtDNA copy number (mtDNA-CN) and increased mutations render impaired mtDNA integrity, causing cellular dysfunction during aging [75]. A calculation of mtDNA-CN by the relative ratio of DNA from the mitochondrial gene NADH dehydrogenase subunit to the nuclear gene cytochrome P4501A1 found that mtDNA-CN decreased in angiotensin (Ang) II-induced cardiac hypertrophy mice [70].…”
Section: Oxidative Damage To Mitochondrial Dna Copy Numbermentioning
confidence: 99%
“…These data also add to the current understanding of PolG mice in particular. Previous studies found that mtDNA copy number decreases with age (5,30). Our results showed slightly decreased mtDNA copy number with age, though it was not statistically significant.…”
Section: Discussionmentioning
confidence: 91%
“…As a result, PolG mice accumulate mitochondrial DNA (mtDNA) mutations leading to premature aging phenotypes including hair loss, weight loss, kyphosis, increased rates of apoptosis, organ damage, and eventually, an early death at around 12 months (24). PolG animals have also been reported to have a depletion of mtDNA copy number (4), or the number of mtDNA molecules per nuclear genome, which is generally associated with a decrease in mitochondria and energy production (4,5).…”
Section: Introductionmentioning
confidence: 99%